The political activity of Sayyid Tariq bin Taimur and his attempts to implement constitutional rule in Oman (1967-1970) - Bait Fadhil, Suad (Al-Adab Journal, 2023)
There is no doubt that Oman during the time period covered by the study witnessed several changes that eventually led to the change of the ruling authority in the country. This study examines the first attempts to draft a written constitution in Oman and the internal position thereon. The research is divided into several main sections. The first is devoted to the identification of Sayyid Tariq Bin Timur’s character. The second research follows the beginning of the emergence of constitutional theory by Sayyid Tariq Bin Timur in Oman, the third was to clarify the internal position against the policy of Sultan Said bin Timur despite his attempts to rectify the financial situation in Oman, which led to his disqualification from rule as it explained in the fourth research. The fifth research focused on Sayyid Tariq bin Taimur’s desire to make Oman a constitutional kingdom, his repeated attempts to establish constitutional concepts in Oman, and his adherence to his position on the constitution until he decided to retire from political life. The study ended with a conclusion that included the most important findings of the study, which were summarized in highlighting the importance of having a written constitution to organize state affairs. 2.12.0.0 2.12.0.0